Experimental study of the drying of sugar cane bagasse - Villalba Vidales, Jorge; Arzola de la Peña, Nelson (Scientia et Technica, 2019)
Optimizing biomass drying to improve combustion processes is one of the main tools available to small and medium agroindustrial producers in rural areas of Colombia to be competitive. For this reason, the development of experimental studies becomes a priority to improve the competitiveness of the rural sector in Colombia. In this way this paper shows the development of the experimental study of drying kinetic of panelera’s sugar cane bagasse, as well as its contrast with mathematical models used for the prediction of the drying kinetics. The results obtained can be useful as a reference for the effective design of sugarcane bagasse drying systems.